Molecular characterization of the iron binding protein ferritin in Eisenia andrei earthworms - Procházková, Petra; Dvořák, Jiří; Šilerová, Marcela; Roubalová, Radka; Škanta, František; Halada, Petr; Bilej, Martin (Gene, 2011)
Ferritin is a storage protein that plays a key role in iron metabolism. In this study, we report on the sequence characterization of a ferritin-coding cDNA in Eisenia andrei earthworms isolated by RT-PCR using degenerated primers, and we suggest the presence of a putative IRE in the 5'-UTR of ferritin mRNA. The obtained ferritin sequence was compared with those of other animals showing sequence and structure homology in consensus sites, including the iron-responsive element (IRE) and ferroxidase centers. Despite the sequence homology in the E. andrei mRNA of ferritin with the sequences of other animals in consensus IRE sites, the presented cytosine in the IRE of E. andrei ferritin in the expected position does not form a conventional bulge. The presence of ferritin in the coelomic fluid of E. andrei was proven by iron staining assay. Moreover, aconitase activity in the coelomic fluid was assessed by aconitase assay, suggesting the presence of an iron regulatory protein. Quantitative analysis revealed changes in the gene expression levels of ferritin in coelomocytes in response to bacterial challenge, reaching the maximum level 8h after the stimulation with both Gram-positive and Gram-negative bacteria.
Keywords: Molecular Sequence Data; messenger RNA; Sequence Analysis, DNA; konformace nukleové kyseliny; sekvence aminokyselin; Nucleic Acid Conformation; DNA, Complementary; Gene Expression Regulation; ceruloplasmin; Escherichia coli K12; DNA primery; akonitáthydratasa; Cloning, Molecular; RNA; Bacillus subtilis; Ceruloplasmin; regulace genové exprese; polymerázová řetězová reakce s reverzní transkripcí; Base Sequence; sekvence nukleotidů; Oligochaeta; komplementární DNA; zvířata; RNA, Messenger; Amino Acid Sequence; sekvenční analýza DNA; klonování DNA; Reverse Transcriptase Polymerase Chain Reaction; molekulární sekvence - údaje; DNA Primers; ferritiny; Aconitate Hydratase; Ferritins; Animals